PERLAWANAN DAN PERTUNJUKAN POLITIK (AKSI COR KAKI MASYARAKAT KENDENG DI DEPAN ISTANA NEGARA PADA TAHUN 2016) - Afifah, Dewi; Erawan, I Ketut Putra; Pramana, Gede Indra (Jurnal Nawala Politika, 2023)
This study aims to describe the action of the people of Kendeng who locked their feet with cement in front of Istana Negara. This action is a  form of resistance by the people of Kendeng against the construction of a cement mining industry in the North Karst Kendeng Mountains, Central Java. This study argues that the resistence is considered a form of staging politic, with various ways in which the state and society in interact and negotiate. The gender dimension’s existence attemps to emerge as a symbol of resistence, portraying women farmers as embodiments of Mother Earth. This novelty is presented to highlight the political affects of emotion involvement in every action, which is shown to strongly influence the audience. To examine these cases, this study employs the theory of staging politic and the concept of Performance For Power. Keywords: Resistance,Political Performance, and Performance for Power This study aims to describe the action of the people of Kendeng who locked their feet with cement in front of Istana Negara. This action is a  form of resistance by the people of Kendeng against the construction of a cement mining industry in the North Karst Kendeng Mountains, Central Java. This study argues that the resistence is considered a form of staging politic, with various ways in which the state and society in interact and negotiate. The gender dimension’s existence attemps to emerge as a symbol of resistence, portraying women farmers as embodiments of Mother Earth. This novelty is presented to highlight the political affects of emotion involvement in every action, which is shown to strongly influence the audience. To examine these cases, this study employs the theory of staging politic and the concept of Performance For Power. Keywords: Resistance,Political Performance, and Performance for Power